The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acs.inorgchem.9b01740
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulating Halometallates into 3-D Lanthanide-Viologen Frameworks: Controllable Emissions, Reversible Thermochromism, Photocurrent Responses, and Electrical Bistability Behaviors

Abstract: The encapsulation of guests into metal−organic frameworks (MOF) is an efficient strategy to generate novel multifunctional materials with enhanced properties. Herein, four halometallate@MOF composites with formulas of {(Pb 2 I 4 Br 3 ) [(Pr(bpdo) [(La(bpdo) 4 (H 2 O) 2 ] 2 } n (4) (bpdo = 4,4′-bipyridine N,N′-dioxide) were prepared. In these composites, lanthanide-viologen MOF act as matrices, whose cavities were penetrated by halometallates. Consequently, the insertion of electron-rich halometallates into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 88 publications
2
45
0
Order By: Relevance
“…16,17 Therefore, the reaction of lanthanide ions with suitable ligands has become an effective way to construct multifunctional lanthanide-based MOFs (Ln-MOFs). 18,19 In particular, the photoluminescence characteristics of Ln-MOFs expand the application in molecular switches and chemical sensors. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Many Ln-MOFs have been applied to detect metal cations, inorganic anions and small organic molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Therefore, the reaction of lanthanide ions with suitable ligands has become an effective way to construct multifunctional lanthanide-based MOFs (Ln-MOFs). 18,19 In particular, the photoluminescence characteristics of Ln-MOFs expand the application in molecular switches and chemical sensors. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Many Ln-MOFs have been applied to detect metal cations, inorganic anions and small organic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 In particular, the photoluminescence characteristics of Ln-MOFs expand the application in molecular switches and chemical sensors. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Many Ln-MOFs have been applied to detect metal cations, inorganic anions and small organic molecules. 25,26 However, there are few reports of Ln-MOFs for the detection of amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…Following the memristive mechanism of the ejection and trapping of charges induced by the conversion between Ohmic and SCLC mode, halometallate-embedded MOF film devices displayed bistability and resistive switching characteristics with an ON/OFF ratio of 10 3 . 95 The halometallate-embedded MOFs ({[Pb 3 I 10 (H 2 O) 2 ][Y 2 (bpdo) 5 (OH) 2 ]•4(H 2 O)} n and {(Bi 2 I 9 )[(Pr(bpdo) 3 (H 2 O)]} n ) were synthesized by the solvothermal method in an autoclave. These solutions were spin-coated on a polymer-coated ITO substrate, and then Ag electrodes were deposited to fabricate the memristive device.…”
Section: Reticular Materials Thin-film-based Resistive Switching Devicesmentioning
confidence: 99%
“…As heterogeneous MOF composite film-based RS devices operated by Ohmic and SCLC mode above-mentioned, 63,95 a kind of MOF thin film itself, mechanically robust [Cu 2 I 2 (TAA)] n film, prepared by the Langmuir-Schafer technique, exhibited memristive behavior presenting pinched hysteresis with an ON/OFF ratio up to 30 and sweeping speeds below 0.3 V/s. 81 Liu et al 59 reported that the ZIF-8 thin film could show nonvolatile resistive switching characteristics with the fabricated sandwiched device structure of Ag/ZIF-8/Si (Figure 7a).…”
Section: Reticular Materials Thin-film-based Resistive Switching Devicesmentioning
confidence: 99%
“…2,3 Recently, as a photoactive component with strong electron-accepting behaviors, excellent redox characteristics and sensitive photo/thermal chromisms, viologens have been widely used in the construction of functional charge-transfer (CT) complexes, whose electron transfer processes were accompanied by simultaneous generation of free radicals. [4][5][6][7] However, some disadvantages have emerged in viologen-based composite materials, including slow photo-responsibility and reversibility. 4 Therefore, modifications of viologens, including the introduction of π-conjugated substituents as electron donors and stabilizers, have been conducted.…”
Section: Introductionmentioning
confidence: 99%